Literature Review : Pengaruh Pemberian Aromaterapi Lemon terhadap Penurunan Hiperemesis Gravidarum pada Ibu Hamil Trimester I : Literature Review - Nurfitriyani , Dewi; Sukyati, Ira (Maternal & Neonatal Health Journal, 2026)
Hyperemesis gravidarum is a condition of severe nausea and vomiting that commonly occurs in the first trimester of pregnancy, which can cause dehydration and electrolyte disturbances. One non-pharmacological management to reduce this complaint is the use of easy-to-use lemon aromatherapy. To determine the effect of lemon aromatherapy on reducing hyperemesis gravidarum in pregnant women in the first trimester, conduct a critical review and gain knowledge about the effect of lemon aromatherapy on reducing hyperemesis gravidarum in pregnant women in the first trimester. Literature review by reviewing various studies of others with criteria set by the research, namely with systematic inclusion and exclusion criteria by searching using Google Scholar. Based on the 5 articles reviewed, routinely administering lemon aromatherapy every morning as a non-pharmacological therapy to reduce hyperemesis gravidarum in pregnant women in the first trimester because it contains orange compounds that control pain and hormonal balance. It can be concluded that there is an effect of lemon aromatherapy on reducing hyperemesis gravidarum in pregnant women in the first trimester